The age and the growth of the european weather loach (Misgurnus fossilis) - Fazekas, Gergely; Harangi, Sándor; Vass, Nóra; Oláh, János (Acta Agraria Debreceniensis, 2009)
The possibilities of examination the growth of fish species are verry difficult, and much of methods are oblique. With the weather loach is the work especially complicated through the small scales. Till now the growth of weather loach is in Hungary unexamined. We applied self developed catch method in three explored channel. The length and weight measured on the fishes alive, as well the sexing. We analysed the datas with Bertalanffy-method. The growth of the fishes is different, but the growth of the body length was nearly the same in the three channels. The one year old fishes can growth to a maximum of 130-140 millimeters, the two years old fishes can growth to maximum of 180-190 millimeters. Longer fishes by 180-190 millimeters are 3 or more years old. The data of sex-ratio is deviant than the literature wroted. The fish from Fényes are growing faster, than the others. This species can be 190-200 millimeters long after 2 years from birth. It is a very fast growing.